2010
DOI: 10.1016/j.pec.2009.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Multiple health behavior clusters among female college students

Abstract: Objective To examine prevalence of multiple unhealthful behaviors and detect clusters of unhealthful behaviors among college women. Methods Women ages 18–22 enrolled full-time at an urban university located in the Northeastern United States were invited to complete an online survey, which assessed maintenance behaviors: fruits/vegetables, physical activity, cervical screening and at-risk behaviors: frequent drinking, smoking, and non-use of protective measures during sexual intercourse. Of 4774 invited, comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
23
1
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 18 publications
8
23
1
9
Order By: Relevance
“…We have reported such collections (gathering) of 'favourable' or 'less/un favourable' health factors and practices elsewhere (58), and have further suggested the relationships of such findings with macro-level aspects such as income, gender issues, political models, and social rights which could act as mediatory factors that might moderate attitudes (33). In agreement, others (3,4) have reported similar clustering where, at the individual person level, habits and practices or (healthy and unhealthy) behaviours could cluster in certain individuals.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…We have reported such collections (gathering) of 'favourable' or 'less/un favourable' health factors and practices elsewhere (58), and have further suggested the relationships of such findings with macro-level aspects such as income, gender issues, political models, and social rights which could act as mediatory factors that might moderate attitudes (33). In agreement, others (3,4) have reported similar clustering where, at the individual person level, habits and practices or (healthy and unhealthy) behaviours could cluster in certain individuals.…”
Section: Discussionsupporting
confidence: 71%
“…Further, multiplicative detrimental effects can be expected when unhealthy behaviours cluster together. For instance, about 65% of full-time female students (18)(19)(20)(21)(22) years old) at an urban university in the USA exhibited two or more unhealthy behaviours (3), and a cluster analysis on health behaviours among German students indicated that about one quarter of students displayed clustered risks in terms of their behaviours (4). Indeed studies have suggested that students' lifestyles and risk behaviours during the university period raise concern and comprise many issue.…”
Section: Introductionmentioning
confidence: 99%
“…These women have a significantly greater risk for secondary cancers related to both human papilloma virus (HPV) and smoking (Chaturvedi et al, 2007). This finding may be related also to clusters of high-risk health behaviors, such as drinking, smoking, and unprotected sex (leading to HPV infection), as seen in female college students (Quintiliani, Allen, Marino, Kelly-Weeder, & Li, 2009). This high-risk population should be targeted for tobacco use assessment and interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Ações em promoção da saúde devem reconhecer os fatores de risco relacionados ao início da experimentação do tabaco, sem desconsiderar os fatores de proteção do indivíduo a fim de extrapolar para aspectos relacionados à família e aos recursos comunitários 2 e integrar a abordagem de outros hábitos saudáveis na prevenção e controle do tabagismo entre jovens universitários 7,18,19 . Nesse sentido, não se exclui a importância de proteger a própria saúde dos prejuízos e das doenças tabacorelacionadas e ter maior controle sobre si na evitação do consumo do tabaco conforme mencionado pelos participantes dessa pesquisa.…”
Section: Discussionunclassified